TAVI-prosthetic valve endocarditis can often be cured without surgery. (3rd October 2022) - Ried, I; Omran, H; Rudolph, T K; Scholtz, S; Bleiziffer, S; Piper, C
Abstract: Introduction: Prosthetic valve endocarditis (PVE) is the most unfavourable complication after any aortic valve replacement. Purpose: The aim of this study was to analyse the impact of antibiotic-only and additional surgical therapy in patients with TAVI-PVE and to compare it with the results of patients with PVE after surgical aortic valve replacement (SAVR) regarding survival. Methods: All patients who underwent primary isolated aortic valve replacement via SAVR (n=3.447) or TAVI (n=2.269) in our heart center between 01/2012–12/2018 were analysed. The diagnosis of PVE was made using the 2015 modified Duke criteria. Follow-up was performed until 06/2019 (max. 89, mean 34 months) with a follow-up rate of 98% regarding mortality. Results: PVE incidence did not differ significantly between SAVR with 4.9 cases per 100 patient-years and TAVI with 2.4 cases per 100 patient-years (p=0.49), although TAVI patients were significantly older (mean 80 vs. 67 years) and had more multimorbidities (STS score mean 5.9 vs. 1.6) (p<0.001). TAVI prostheses with polymer showed a 4.3-fold higher risk to develop PVE than TAVI prostheses without polymer (p=0.004). Most common pathogens were staphylococci and enterococci in all PVEs. Antibiotic-only therapy in TAVI-PVE patients resulted in a significantly better 1-year survival compared with additional surgical therapy (90.9% vs. 33.3%; p=0.005) even in 4 patients with an indication for surgery according to ESC guidelines. In SAVR-PVE patients both therapies led to comparable survival (p=0.861). However, SAVR-PVE who were not operated although indication for surgery was given by the guidelines resulted in a significantly worse survival after 1 year (p=0.004). Conclusion: TAVI patients did not have a significantly higher risk to develop PVE than SAVR patients despite their older age and greater comorbidities. The 1-year survival of TAVI-PVE patients was significantly higher after antibiotic-only therapy than after additional surgery, even if surgery had been indicated according to guidelines. This new finding is presumably due to the fact that TAVI prostheses do not have a polymeric suture ring. Our results show for the first time that indication for surgery in TAVI-PVE patients should be made carefully. SAVR-PVE patients however benefit from guideline-compliant surgery as in this respect antibiotics-only led to a significantly worse prognosis. This is probably related to the ability of gram-positive cocci to migrate into the polymeric ring and to protect themselves from antibiotic therapy by forming a biofilm. Some of the newer TAVI prostheses contain plastic components which can also be cured often with antibiotic-only but are associated with an increased risk to develop PVE. Funding Acknowledgement: Type of funding sources: None.